Transformative Learning & Teaching Delivery Through Flipped Learning - Mohd Ridhuan, Mohd Sharip; Shafrida, Sahrani; Siti Kudnie, Sahari; Kho, Lee Chin; Dyg Norkhairunnisa, Abang Zaidel (Centre for Applied Learning and Multimedia, 2020)
Higher education has come to shift towards more flexible, effective, active and student-centered teaching strategies that soften the limitation of conventional teaching delivery. Flipped classroom approach is one of the student to centered learning approaches to create effective teaching and learning. This initiative leads students to employ higher order thinking skills (HOTs)in their learning activities and as a motivation for them to fulfil their own learning goals.